Developments on auxetic closed cell foam pressure vessel fabrications. (1st July 2022) - Duncan, O; Leslie, G; Moyle, S; Sawtell, D; Allen, T
Abstract: Auxetic foam can have higher indentation resistance, better protection under impact and higher vibration damping than conventional foam. Unlike auxetic open cell foam, with established, commercially viable options for manufacturing, methods for making auxetic closed cell foam are not established. We revisited pressure-vessel methods, proposed in 1996, for making auxetic closed cell foam. We processed low-density polyethylene foam for 6 h at 400–700 kPa and 100 °C, causing foams to shrink by a factor of two to five. The volumetric compression kinked cell walls, producing negative Poisson's ratios as low as −0.2 and Young's moduli from 0.2 to 1.2 MPa. Trends between applied volumetric compression and Poisson's ratio agree with those for open cell foam—initially decreasing to negative values as volume reduced by a factor of two after processing, then plateauing or slightly increasing as volume decreased by a factor of two to five. Foams of different sizes and shapes (15–75 mm sides) processed in the same conditions (700 kPa, 6 h, 100 °C) shrank evenly in all three axes and had similar final volume ratios. We noticed a long settling period, of up to three months, where foams slowly shrank. Placing foam in a vacuum after processing reduced the settling period to within 24 h.